Comparison of tools for assessing fatigue in patients with heart failure - Eliane Nepomuceno; Luma Nascimento Silva; Débora Cristine Prévide da Cunha; Rejane Kiomi Furuya; Marcus Vinicius Simões; Rosana Aparecida Spadoti Dantas
ABSTRACT Objective: To compare the distributions of measurements of the Dutch Fatigue Scale (DUFS), Dutch Exertion Fatigue Scale (DEFS), and Fatigue Pictogram tools, according to the New York Heart Association (NYHA) Functional Classification and left ventricular ejection fraction (LVEF). Method: Methodological, cross-sectional study with 118 patients with heart failure. Variance analysis, Pearson's correlation, and Fisher's exact tests were carried out, with a significance level of 0.05. Results: There was an increase in the DUFS and DEFS means with worsening of the NYHA-FC (p<0.001, for both tools). Correlations among the LVEF resulted in positive and weak magnitude for the DEFS (r=0.18; p=0.05) and for the DUFS (r=0.16; p=0.08). Just the item A on the Fatigue Pictogram had an association with the NYHA-FC (p<0.001) and the LVEF (p=0.03). Conclusion: Three tools detected worsening in fatigue levels according to the illness severity assessed by the NYHA-FC.